2020
DOI: 10.1021/acssuschemeng.0c04842
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Cellulose Nanofibrils Decorated with Ag Nanoparticles and Their Application in Colorimetric Detection of l-Cysteine

Abstract: In this study, we reported an environmentally benign method for the synthesis of silver nanoparticles (AgNPs) by using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized cellulose nanofibrils (CNFs) as the only reducing agent and stabilizer under mild aqueous conditions. The AgNPs were tightly adhered to the CNF surface, and the resulting stable CNF–AgNP suspension can be used for rapid and selective detection of l-cysteine (Cys). The efficacy of the process relies upon the surface plasmon resonance propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 55 publications
(75 reference statements)
2
27
0
Order By: Relevance
“…Sajadi et al [84] utilized polyphenolic substances, such as flavonolignans, from Silybum marianum L. seed extracts to reduce copper ions to CuNPs and their own structure was transformed from keto to enol, as shown in Figure 3. Yu et al [135] used nanocellulose to synthesize AgNPs, where positively charged silver ions were attracted to negatively charged carboxyl and hydroxyl groups on nanocellulose. At 80°C, the silver ions were reduced by the hydroxyl groups, which themselves were oxidized to aldehyde groups.…”
Section: Chemical Mechanisms Of Metal Nanoparticle Synthesis Using Plant Extractsmentioning
confidence: 99%
“…Sajadi et al [84] utilized polyphenolic substances, such as flavonolignans, from Silybum marianum L. seed extracts to reduce copper ions to CuNPs and their own structure was transformed from keto to enol, as shown in Figure 3. Yu et al [135] used nanocellulose to synthesize AgNPs, where positively charged silver ions were attracted to negatively charged carboxyl and hydroxyl groups on nanocellulose. At 80°C, the silver ions were reduced by the hydroxyl groups, which themselves were oxidized to aldehyde groups.…”
Section: Chemical Mechanisms Of Metal Nanoparticle Synthesis Using Plant Extractsmentioning
confidence: 99%
“…Electrospinning and chemically synthesized CNFs can serve as nanoscale templates for the preparation of various CNF-based 1D nanomaterials. The surface of CNFs could be functionalized first with suitable chemicals and then achieved in combination with nanoparticles [ 25 , 26 , 27 , 28 , 29 , 30 ], quantum dots [ 31 , 32 ], metal-organic frameworks (MOF) [ 32 , 33 ], carbon nanotubes (CNTs) [ 34 ], and others.…”
Section: Fabrication Of Cnf-based 1d 2d and 3d Functional Materialsmentioning
confidence: 99%
“…The obtained results indicated that the bound alkali lignin improved the antioxidant activity of CNFs, and the in situ synthesized CuO nanoparticles improved the performance against both E. coli and S. aureus bacteria, showing the potential application of the designed CuO/CNF materials for wound dressing. With the similar methods, various nanoparticles, such as Ag [ 26 , 29 , 30 ], TiO 2 [ 27 ], Ag@Au [ 28 ], and Cu [ 29 ], have been synthesized on CNFs for different applications. In addition to NPs, the quantum dots, such as carbon dots [ 31 ] and black phosphorus quantum dots [ 32 ], have been anchored onto the surface of CNFs to form 1D CNF fluorescent nanomaterials.…”
Section: Fabrication Of Cnf-based 1d 2d and 3d Functional Materialsmentioning
confidence: 99%
“…Moreover, it is convenient to operate, cost-effectiveness, and rapid detection. [28] Presently, various nanomaterials including Cu metalloenzyme, [33] Co 3 O 4 , [34] Au, [30] and Carbon Quantum Dots [23] have been reported for Cys and GSH detection through colorimetric method, however, the material preparation is complicated and required rigorous conditions, for example, high temperature and high pressure. Therefore, to prepare novel functional materials at a moderate condition without using toxic solvents and investigate its applications in Cys and GSH detection needed further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…[27] The quantification of Cys is important for accurate prediagnosis of its related disease such as cancer, cardiovascular and cerebrovascular disease. [28] Glutathione (GSH), a thiol-containing tripeptide (l-glutamic acid, l-cysteine, and glycine), is extensively distributed in mammalian and eukaryotic cells. [29] In the tissues, the tripeptide has two forms: reduced (GSH) and oxidized form (GSSH), which maintain the intracellular reduction-oxidation potential.…”
mentioning
confidence: 99%